Okur‐Chung neurodevelopmental syndrome: Eight additional cases with implications on phenotype and genotype expansion. Issue 4 (13th February 2018) - Chiu, A.T.G.; Pei, S.L.C.; Mak, C.C.Y.; Leung, G.K.C.; Yu, M.H.C.; Lee, S.L.; Vreeburg, M.; Pfundt, R.; van der Burgt, I.; Kleefstra, T.; Frederic, T.M.‐T.; Nambot, S.; et al.
Abstract : Okur‐Chung syndrome is a neurodevelopmental condition attributed to germline CSNK2A1 pathogenic missense variants. We present 8 unreported subjects with the above syndrome, who have recognizable dysmorphism, varying degrees of developmental delay and multisystem involvement. Together with 6 previously reported cases, we present a case series of 7 female and 7 male subjects, highlighting the recognizable facial features of the syndrome (microcephaly, hypertelorism, epicanthic fold, ptosis, arched eyebrows, low set ears, ear fold abnormality, broad nasal bridge and round face) as well as frequently occurring clinical features including neurodevelopmental delay (93%), gastrointestinal (57%), musculoskeletal (57%) and immunological (43%) abnormalities. The variants reported in this study are evolutionary conserved and absent in the normal population. We observed that the CSNK2A1 gene is relatively intolerant to missense genetic changes, and most variants are within the protein kinase domain. All except 1 variant reported in this cohort are spatially located on the binding pocket of the holoenzyme. We further provide key recommendations on the management of Okur‐Chung syndrome. To conclude, this is the second case series on Okur‐Chung syndrome, and an in‐depth review of the phenotypic features and genomic findings of the condition with suggestions on clinical management. Abstract : Summary of all reported CSNK2A1 variations in Okur‐Chung neurodevelopmental syndrome. Most of the variations are located within the protein kinase domain of the gene, with position 198 being a mutation hotspot.